(untitled) (Research, Society and Development, 2021)
Objective: this study aims to characterize the clinical complaints and imaging findings in musculoskeletal disorders related to work (RSI). Method: this is a descriptive, exploratory, and cross-sectional research, conducted from October 2008 to September 2009 in a Reference Center for Occupational Health, with a sample of 60 subjects. We performed a separate interview, using a questionnaire and a roadmap for analysis of tests. Results: the population was mostly male (66.7%), the profession most affected was the machine operator (18.3%), the most frequently reported complaints were pain (100%) and lack of strength (93.3%). The most cited were the shoulder D (26.5%) and lumbar spine (37.5%). The most used tests for the diagnosis were ultrasonography (38%) and magnetic resonance (36.5%). The most found changes in tendons, muscles, synovias and bursas – inflammations (10.3%) and calcifications (11.2%) - and in vertebral discs - disc protusons (13.1%) and presence of osteophytes (10.3%). A significance level p< 0.05 and confidence interval (CI) of 95% were considered for the calculations of frequencies. Conclusion: in view of the vulnerability of workers to disorders, it is important to value the patient’s clinical complaints and the information contained in imaging exams, with the purpose of having an early clinical diagnosis and assisting health professionals to enable the most appropriate therapy.